Theodore and Diodore’s heritage: the Greek original, Syriac and Latin translations - Evgenii Zabolotnyi (Вестник Православного Свято-Тихоновского гуманитарного университета: Сериа III. Филология)
The article researches the Christological fragments from the writings of Diodore of Tarsus and Theodore of Mopsuestia, preserved both in the Greek original and in the Syriac and Latin translations. Comparison of these fragments will allow to get closer to solving the problem of interpolations in the versions that have come down to us. A comparative analysis of these versions makes it possible to reconstruct and refine Theodore’s Christological formula and also demonstrates that the Syriac and Latin intellectuals followed the pattern of transltaion of the Greek theological terminology, which can be called “standard”. Moreover, the translation activity, which took place in the 5th century in the School of Edessa and resulted in preparing translation of Theodore’s most important Christological treatise, De Incarnatione, into the Syriac, made a great contribution to the formation of the “standard” translation scheme. The author shows that this translation is the best witness to the text of De Incarn. VIII 62, rather than the quotations of the opponents of Antiochene Christology, who apparently based on the florilegium, which contained interpolations. As a result, the article studies in a detailed manner the translation technique used by Christian intellectuals from the 5th to the 6th centuries, including those who worked in the Syriac educational centers. The Latin versions of these fragments will also be considered not in isolation, but in the context of the development of Western theological terminology.